Current State and Novel Approaches of Antiplatelet Therapy. Issue 6 (June 2015) - Metharom, Pat; Berndt, Michael C.; Baker, Ross I.; Andrews, Robert K.
<x xml:space="preserve">Abstract</x> An unresolved problem with clinical use of antiplatelet therapy is that a significant number of individuals either still get thrombosis or run the risk of life-threatening bleeding. Antiplatelet drugs are widely used clinically, either chronically for people at risk of athero/thrombotic disease or to prevent thrombus formation during surgery. However, a subpopulation may be resistant to standard doses, while the platelet targets of these drugs are also critical for the normal hemostatic function of platelets. In this review, we will briefly examine current antiplatelet therapy and existing targets while focusing on new potential approaches for antiplatelet therapy and improved monitoring of effects on platelet reactivity in individuals, ultimately to improve antithrombosis with minimal bleeding. Primary platelet adhesion-signaling receptors, glycoprotein (GP)Ib-IX-V and GPVI, that bind von Willebrand factor/collagen and other prothrombotic factors are not targeted by drugs in clinical use, but they are of particular interest because of their key role in thrombus formation at pathological shear.